Pengaruh Beban Kerja, Disiplin Kerja dan Kompensasi Terhadap Kinerja Karyawan - Endang Sri Wahyuningsih; Andhi Johan Zusana (FEB UNWIKU PURWOKERTO, 2021)
Human resources have a very important role in every business activity, so that every form of business activity or organization requires the support of reliable human resources. The purpose of this study was to determine whether workload, work discipline and compensation have an effect on employee performance. The population of this study were employees of UD Margo Mulyo in Purwokerto. The sampling technique was simple random sampling using the Slovin formula. There were 60 respondents. The method of analysis uses multiple linear regression analysis. The results showed that work discipline and compensation had a positive and significant effect on employee performance, while workload have a negative but not significant effect on employee performance. Leaders should pay attention to workload, work discipline and employee compensation in order to be optimal in achieving their business goals